2019
DOI: 10.1016/j.carbon.2018.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Graphene multi-protonation: A cooperative mechanism for proton permeation

Abstract: The interaction between protons and graphene is attracting a large interest dueto recent experiments showing that these charged species permeate through the 2D material following a low barrier (∼ 0.8 eV) activated process. A possible explanation involves the flipping of a chemisorbed proton (rotation of the C-H + bond from one to the other side of the carbon layer) and previous studies have found so far that the energy barriers (around 3.5 eV) are too high to explain the experimental findings. Contrarily to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…This provides further support to the view that the activation barriers found for proton transport through high-quality graphene and hBN do not involve vacancies and other atomic-scale defects 1 , a conclusion important for further theory developments (e.g., for the hydrogenation model proposed in refs. 8,9 ). Our results also have implications for the widely discussed use of atomically thin crystals as a novel platform for various separation technologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides further support to the view that the activation barriers found for proton transport through high-quality graphene and hBN do not involve vacancies and other atomic-scale defects 1 , a conclusion important for further theory developments (e.g., for the hydrogenation model proposed in refs. 8,9 ). Our results also have implications for the widely discussed use of atomically thin crystals as a novel platform for various separation technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Proton transport through two-dimensional (2D) crystals has recently been studied, both experimentally and theoretically 19 . As for the experiment, it was found that proton permeation through mechanically exfoliated crystals is thermally activated with energy barriers of ≈0.8 eV for graphene and ≈0.3 eV for monolayer hexagonal boron nitride (hBN) 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments [ 6,7 ] demonstrated that single atom‐thin membranes of mechanically exfoliated graphene and hexagonal boron nitride ( h BN) are permeable to thermal protons (H + ), but much less so to deuterons (D + ), resulting in a room‐temperature separation factor of about 10, much higher than in the conventional separation methods. [ 5 ] These interesting findings are discussed somewhat controversially, both on theoretical [ 8–12 ] and experimental [ 10,13,14 ] grounds. The underlying question is whether or not thermal protons can permeate through perfect 2D membranes.…”
Section: Figurementioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) have attracted much interest in their synthesis and aromatic property . Protonated PAHs have been researched as cationic reactive intermediates in a number of reactions, as models of protonated graphene and nanotubes, and as species in the interstellar medium . Their aromaticity is an important feature to understand the electronic properties of cyclic π‐conjugated systems.…”
Section: Introductionmentioning
confidence: 99%